A theory of Bayesian decision making - Edi Karni (The Johns Hopkins University, Department of Economics, 2009)
This paper presents a complete, choice-based, axiomatic Bayesian decision theory. It introduces a new choice set consisting of information-contingent plans for choosing actions and bets and subjective expected utility model with effect-dependent utility functions and action-dependent subjective probabilities which, in conjunction with the updating of the probabilities using Bayes' rule, gives rise to a unique prior and a set of action-dependent posterior probabilities representing the decision maker's prior and posterior beliefs.
Keywords: D80; D81; D82; 330; Bayesian decision making; subjective probabilities; prior distributions; beliefs